Contrast Enhancement of Medical Images: A Review - Singh, Shankar; Pal, Pravesh (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
This paper studies various research contributions in the field of contrast enhancement of medical images. Medical images such as X-rays, ultrasound and others are used in the analysis and diagnosis process by physicians and radiologists. If the image quality is not good and contrast is poor then the diagnosis result is badly affected. Therefore, this paper attempts to review the research papers on contrast enhancement and recommend some viable solution to the challenges in existing research works.